From physical to virtual: a new learning norm in music education for gifted students - Ismail, Md Jais; Anuar, Azu Farhana; Loo, Fung Chiat (Athabasca University Press, 2022)
Music education is a subject that is generally thought to have much physical activity involved. However, virtual learning has been mandatary applied to most schools worldwide due to the COVID-19 pandemic. The landscape of music learning has had to be switched to online distance learning (ODL), where students learn music virtually using technological tools. Gifted students are among those affected by the implementation of music ODL throughout 2020. Thus, the purpose of this study is to identify the effectiveness of music ODL on gifted students’ motivation. The researchers framed this quantitative study by involving 81 secondary gifted students, aged 13 years, from 13 states in Malaysia. The sample was selected through random sampling, and a preexperimental design was applied to conduct the study. Respondents had been exposed to the music ODL intervention for a month. Data were collected through an adapted questionnaire, namely, the MUSIC Inventory, with a five-point scale. Data were further analysed by descriptive and inferential statistics, integrating two-way MANOVA, using SPSS Statistics version 23. Results reveal that an ODL approach to music classes is significantly effective to enhance gifted students’ motivation domains of empowerment, usefulness, success, interest, and caring. Yet, no significant difference was found in gifted students’ genders and locations on the four domains. Different approaches in music teaching could be further explored for music ODL to gifted students in future studies.